Penggunaan Pendekatan Kooperatif Tipe Jigsaw Dalam Peningkatan Hasi Belajar Mahasiswa Pada Mata Kuliah Praktikum IPA - Indah Pratiwi (Keguruan, 2022)
This study aims to determine the increase in science learning outcomes by using a jigsaw cooperative type in science practicum courses in class II F. This research was conducted in an elementary school with a total of 21 students. This research is very necessary in applying the jigsaw type cooperative approach to science practicum courses. The data obtained include, tests and observation sheets. This classroom action research consists of two cycles. Each cycle consists of 4 stages, namely planning, implementing actions, observing and reflecting, based on the results of research students are given a test of 10 questions. From the results of the initial test, it can be seen that the ability of students to master hibernation material on earthworms in the Science Practicum course is still low, with an average score of 43.3. Of the 21 students there were (28.6%) or 6 students who got complete learning outcomes and (66.7%) or 14 students were in the incomplete or unsuccessful category. From the results of the first cycle of research, it can be seen that the ability of students to master hibernation material on earthworms is still low, with an average value of 62.9. Of the 21 students, there were (57.1%%) or 12 students who got complete learning outcomes and (42.7%) or 9 students were in the incomplete or unsuccessful category. From the results of the second cycle of research, it can be seen that the ability of students to master hibernation material on earthworms has improved better, with an average value of 71.9. Of the 21 students, there were (71.4%) or 15 students who got complete learning outcomes and (28.6%) or 6 students were in the incomplete or unsuccessful category on the subject of science. There was an increase in the assessment in cycle II above the KKM value of 70.